The Case of Alpenrind – The Posting of Workers and the Binding Nature of Portable Document A1 - Peter Schöffmann (Zbornik Znanstvenih Razprav)
The Alpenrind case (C-527/16) revealed opposing positions between the Member States providing services feely across Europe and the Member States fearing for social dumping. A tension the Union is grappling with for a certain time, and that increased in the last years. Many (mostly western) Member States believe that the posting of workers is un-dermining their social standards and hampering their labour markets. They are not con-vinced that Union law provides an adequate level to prevent abusive practices. Therefore, these Member States try to take countermeasures by implementing restrictive legislation: imposing obligations on employers to provide documents and comply with notification requirements. This leads to an additional burden potentially impeding the freedom of movement of workers and services; an effect the Social Coordination Regulations actu-ally intend to prevent.The Alpenrind case deals with two questions regarding the postal rule’s impact on so-cial security coordination. It addresses the condition of non-replacement as well as the binding effect of Portable Document A1. However, set in a broader context, it reveals the inherent contradiction of social security coordination. The Union finds itself having to strike a balance between the freedom to provide services and the protection against social dumping.